Mobile Augmented Reality in Education : Recognition of Electronic Component / classroom learning technology / practical learning technology - Hartawan Abdillah; Mas Ahmad Baihaqi; Dani Hari Tunggal Prasetiyo; Alief Muhammad (Merdeka Malang University, 2024)
The introduction of components in the control system practicum utilizes Augmented Reality using cellular so that students know the types of PLC components that are displayed on cellular screens (smartphones). In this case a combination of real world objects such as PLC (Programable Logic Control) components and virtual objects in the form of text, animation, 3D models or computer-generated videos that will be displayed on smartphone screens so that students feel virtual objects in the practicum room. The test results from the detection of the electronic component objects tested included testing the distance, light intensity and covering some objects, the results of the analysis were almost entirely successful in detecting the object. Except in the dark light detection condition, the intensity cannot be determined. This is because, in a marker-based tracking method, identifying the marker pattern is the most important point. In dark conditions, the pattern obtained will be less than optimal so that in the matching process there will be marker errors, or even objects not identified as in the current experiment